THE ROLE OF ISLAMIC FAMILY GUIDANCE IN BUILDING MUSLIM FAMILY RESILIENCE IN THE DIGITAL ERA - Ahmad Arief; Cut Metia (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The development of digital technology presents both opportunities and challenges for Muslim families in maintaining resilience. This study aims to analyze the resilience patterns of Muslim families in the digital era, identify the challenges encountered, and explain the role of Islamic family guidance in strengthening this resilience. This study employed a qualitative descriptive approach, conducted in Tanjung Sari Village, Deli Serdang Regency. Data were collected through in-depth interviews, observation, and documentation from seven married couples with a marriage duration of 5 to 15 years, and subsequently analyzed using NVivo 12 Pro through thematic coding. The findings indicate that the resilience patterns of Muslim families are built upon effective communication, collaboration among family members, adaptability, and the reinforcement of Islamic values. The primary challenges encountered include digital distractions, weakened communication, and digital parenting conflicts. Furthermore, the study reveals that Islamic values serve as a foundation for stability, whereas Islamic family guidance acts as an integrative mechanism connecting religious values, family communication, and digital adaptation strategies. Consequently, structured Islamic family guidance is crucial to strengthening family resilience against the adverse impacts of the digital era.